HUBUNGAN LINGKUNGAN FISIK KERJA DAN BEBAN MENTAL DENGAN KEJADIAN STRES KERJA PADA PEKERJA LAUNDRY DI PT. SANDANG ASIA MAJU ABADI SEMARANG - Vega Auliasari Ridwan; Ida Wahyuni; Yuliani Setyaningsih (Jurnal Kesehatan Masyarakat (Undip), 2017)
Advances in technology have contributed alot to the positive growth in the industrial economy. Work stress is a condition that arises from the interaction between man and his work and is characterized by human change that forces them to deviate from their normal function.Each work can bring its own burdens to workers both physically, mentally and socially. Factors that cause work stress, include the physical state of uncomfortable working environment (noisy, dusty, smelly, hot and humid temperatures), non-ergonomic work stations, workshifts, long working hours, traffic jams on the way to work, high-risk and dangerous jobs, use of new technology, overloading, and adaptation to new types of work.PT Sandang Asia MajuAbadi is an expansive garment industry company so that the working demands on employees are very high for a good quality products to be marketed. This study aims to analyze the correlation of individual characteristics, physical working environment, mental workload, and work fatigue towards the occurrence of work stress. The study is conducted analytically with cross-sectional approach. The samples involved in this study are 108 laundry workers of the company. Data collected by inquiries filled by respondents, physical working environment and work fatigue measurements. According to the result showed by chi-square tests, the correlating variables are mental workload (p=0,001), working climate (p=0,006), noise level (p=0,043), lighting condition (p=0,031).